PENGARUH CORPORATE GOVERNANCE TERHADAP CORPORATE FINANCIAL FRAUD PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Cindy Ellysa; Marheni, Dewi Khornida (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
This study aims to determine the effect of board size, financial expertise, board independence, rationalization, female board, firm size, leverage ratio (LEV) and asset ratio (ROA) on corporate financial reporting in manufacturing companies listed on the Stock Exchange in 2016 - 2020 The sampling technique used is purposive sampling with a final sample of 80 companies. The analysis used in this research is descriptive statistics and panel regression. The results of this study indicate that the size of the board, financial expertise, board independence, rationalization, and do not have a significant effect on the size of the company's finances. While the financial board has a significant influence on fraud, which means a high number of company ownership can reduce the possibility of an incident, then the leverage ratio (LEV) indicates a high debt so there is a high probability of fraud in the company, assets (ROA) has a high positive significant influence ROA can become pressure for the company so that it is likely to take company actions.